Need for Cost-Effective Orthopedic Treatment in Developing Countries - Joshi, Amit; Regmi, Subhash (Nepal Orthopaedic Association Journal, 2024)
One of the primary barriers to adequate orthopedic treatment is the high cost associated with surgeries, rehabilitation, and medical devices. For many individuals in developing countries, out-of-pocket expenses for such therapies are prohibitively expensive, leading to delays in seeking care and worsening conditions. This financial barrier significantly limits access to necessary orthopedic services in regions with minimal or nonexistent healthcare insurance coverage